Liquid biopsy in central nervous system metastases: a RANO review and proposals for clinical applications. Issue 5 (22nd January 2019) - Boire, Adrienne; Brandsma, Dieta; Brastianos, Priscilla K; Le Rhun, Emilie; Ahluwalia, Manmeet; Junck, Larry; Glantz, Michael; Groves, Morris D; Lee, Eudocia Q; Lin, Nancy; Raizer, Jeffrey; Rudà, Roberta; et al.
Abstract: Liquid biopsies collect and analyze tumor components in body fluids, and there is an increasing interest in the investigation of liquid biopsies as a surrogate for tumor tissue in the management of both primary and secondary brain tumors. Herein we critically review available literature on spinal fluid and plasma circulating tumor cells (CTCs) and cell-free tumor (ctDNA) for diagnosis and monitoring of leptomeningeal and parenchymal brain metastases. We discuss technical issues and propose several potential applications of liquid biopsies in different clinical settings (ie, for initial diagnosis, for assessment during treatment, and for guidance of treatment decisions). Last, ongoing clinical studies on CNS metastases that include liquid biopsies are summarized, and recommendations for future clinical studies are provided.